2020
DOI: 10.1101/2020.03.30.20044099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 transmission in Mainland China is associated with temperature and humidity: a time-series analysis

Abstract: COVID-19 has become a pandemic. The influence of meteorological factors on the transmission and spread of COVID-19 if of interest. This study sought to examine the associations of daily average temperature (AT) and relative humidity (ARH) with the daily count of COVID-19 cases in 30 Chinese provinces (in Hubei fromAdditive Model (GAM) was fitted to quantify the province-specific associations between meteorological variables and the daily cases of COVID-19 during the study periods. In the model, the 14-day expo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
268
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(303 citation statements)
references
References 19 publications
33
268
2
Order By: Relevance
“…[ between an increase in humidity and daily additional COVID-19 infections (Qi et al, 2020). The QQ results of this study show that an increase in humidity does play a significant role in increasing COVID-19 recoveries, consistent with the findings of the earlier studies.…”
Section: Results and Discussion [Insert Table 2 Here]supporting
confidence: 91%
“…[ between an increase in humidity and daily additional COVID-19 infections (Qi et al, 2020). The QQ results of this study show that an increase in humidity does play a significant role in increasing COVID-19 recoveries, consistent with the findings of the earlier studies.…”
Section: Results and Discussion [Insert Table 2 Here]supporting
confidence: 91%
“…Several other recent studies have addressed the relationship between weather and COVID-19 transmission. One study looked at average temperature and relative humidity, but only measured at a provincial level, did not consider solar radiation and rainfall, and did not reach clear public health conclusions [8]. Another study related reproductive numbers in Chinese cities to temperature and humidity and extrapolated those findings worldwide [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were recently investigating the contribution of meteorological conditions on Covid-19 transmission around the world. As shown in Pani et al, 2020 studies from China (Shi et al, 2020;Liu et al, 2020b;Xie and Zhu, 2020;Ma et al, 2020;Qi et al, 2020), Iran (Ahmadi et al, 2020), Spain (Briz-Redón and Serrano-Aroca, 2020), the USA (Bashir et al, 2020;Gupta et al, 2020), Mexico (Méndez Arriaga, 2020), Turkey (Sahin, 2020), Brazil (Auler et al, 2020;Prata et al, 2020), Indonesia (Tosepu et al, 2020), Norway (Menebo, 2020) and also over the globe (Sobral et al, 2020;Wu et al, 2020a) are controversial and the World Health Organization (WHO) highlighted that new investigations are needed to quantitatively assess how the weather in uence the virus spreading. On this topic, Pani et al (2020) results found that water vapor temperature, dew point, absolute and relative humidity show positive signi cant correlation with SARS CoV-19 transmission in Singapore, one of the biggest densely-populated megacities in South-East Asia.…”
Section: Introductionmentioning
confidence: 90%
“…More information about data and data reliability can be found in Pani et al (2020). Besides those variables, following Pani et al (2020) methodology, we retrieved also the absolute humidity (AH, in g m -3 ) through Clausius-Clapeyron equation (Qi et al, 2020;Gupta et al, 2020;Pani et al, 2020) where RH represents the relative humidity and T the temperature. Following Ou-Yang et al 2014and Pani et al (2020), the water vapor (WV, in g kg -1 ) is estimated:…”
Section: Data and Estimationsmentioning
confidence: 99%